Intracranial Venous Pressures Manometry for Patients With Idiopathic Intracranial Hypertension: Under Awake Setting or General Anesthesia - Guo, Xin-bin; wei, Sen; Guan, Sheng (Frontiers in Neurology, 2019)
Background and Purpose Venous sinus stenting is a well acknowledged treatment strategy for patients with high venous sinus pressure gradient across the site of outflow obstruction. It is not clear whether Intracranial venous pressures manometry should be under awake setting or under general anesthesia (GA). The aim of this study is to compare the accuracy of venous manometry performed under general anesthesia or awake setting, and analyzing stenting candidacy should be determined under awake setting or under GA. Methods The manometry results of 32 patients with Idiopathic intracranial hypertension (IIH) were recorded under awake setting and general anesthesia before stenting. Mean venous pressures (MVPs) and trans-stenosis pressure gradients were obtained and compared between awake setting and general anesthesia. Results MVPs and trans-stenosis pressure gradients of 32 patients under GA and awake pressure setting were recorded. MVPs in the superior sagittal sinus, torcula, and transverse sinus were lower in GA group (with no significant difference(P>0.05). MVPs were significantly higher in the sigmoid sinus and jugular bulb under GA group (p<0.05). Mean trans-stenosis pressure gradient was significantly lower under GA group (p<0.05). Conclusions Intracranial venous pressure seems influenced by GA. These findings suggest that candidacy for stenting should be determined after venous manometry was measured while patients are awake.